Toxicity of Diflubenzuron and Temephos on Freshwater Fishes: Ecotoxicological Assays with Oreochromis niloticus and Hyphessobrycon eques - Abe, Flavia R.; Machado, Angela A. [UNESP]; Coleone, Ana C. [UNESP]; da Cruz, Claudinei; Machado-Neto, Joaquim G. [UNESP] (Springer Nature, 2019)
Diflubenzuron (DFB) is a larvicide widely used to control Aedes aegypti populations as an alternative to organophosphates (OPs), with a specific mechanism of action for insects by inhibiting their chitin synthesis. However, DFB is used extensively in urban and rural environments, having the aquatic environment as the major receptor. Thus, the present study aimed to investigate the toxicity of DFB-based formulation and compare it with the toxicity of the OP temephos (TMP)-based formulation, a larvicide still used to control A. aegypti, on freshwater fishes Oreochromis niloticus and Hyphessobrycon eques. Organisms were submitted to acute (48 h) and prolonged (7 days) exposures, in the presence and absence of organic sediment, seeking interactions between chemical and sediment. Histopathological analyses were performed on O. niloticus gills and liver. According to 48-h median lethal concentration (LC50), DFB- and TMP-based formulations were classified as harmful and toxic to fish, respectively, following the Globally Harmonized System of Classification (GHS). After prolonged exposure to sublethal concentrations, DFB-based formulation decreased H. eques body weight at concentrations 272-fold lower than its LC50. Ultrastructural responses of O. niloticus indicated edemas and aneurisms on gills, and hepatocyte hypertrophy and vascular congestion of the liver. TMP-based formulation also induced pyknotic nuclei, which may lead to irreversible necrosis. The addition of organic sediment did not alter the larvicide toxicity, suggesting that larvicides remained available to the organisms. Altogether, these results suggest that as an insect-specific pesticide, DFB still induces mortality and tissue damage in fishes; thus, both larvicides pose risks to fishes.
Keywords: Aedes aegypti; Larvicides; Mortality; Tissue damage